SEJARAH KETATANEGARAAN PASCA PROKLAMASI KEMERDEKAAN 17 AGUSTUS 1945 SAMPAI 5 JULI 1959 DI INDONESIA - Agil Burhan Satia; Cicik Nike Rimayani; Hesti Nuraini (universitas islam darul ulum lamongan, 2019)
A number of historians and legal experts consider that a number of major events in 1945 to 1959 affected the foundations and structures of Indonesian law. Therefore, through a theoretical and legislative approach, this paper discusses the history of Indonesian state administration from August 17, 1945 to July 5, 1959. The author concludes that the history of Indonesian state administration is inseparable from Proklamasi Kemerdekaan 17 Agustus 1945, the birth of UUD 1945, the birth of Konstritusi RIS 1949, Dekrit Presiden 5 Juli 1959, and the change of government system in the constitution. Proklamasi Kemerdekaan 17 Agustus 1945 contained three meanings, namely the sovereignty of the nation, the statement of independence, and efforts to uplift the nation's dignity. The birth of UUD 1945 contains a number of historical facts, namely the presentation of ideas on the basis of the state, the formation of the Draft Constitution and the establishment of UUD 1945. The birth of Konstritusi RIS 1949 included two historic events, namely the Perundingan Linggajati which gave rise to a variety of interpretations of Indonesian-Dutch sovereignty and the Konferensi Meja Bundar (KMB) which resulted in the formation of the United States of the Republic of Indonesia. Dekrit Presiden 5 Juli 1959 which contained the dissolution of the Constituent Assembly, the re-enactment of UUD 1945, and the formation of the MPR. The change in the system of government outlined by the constitution also affected Indonesian state administration.